Communication Pattern Of Yemen Ethnic Society On Inter-Marriage (Qualitative descritptive study of inter-ethnic marriage in Pasar Kliwon Surakarta) - FIKRI, Husin; , Yanti Haryanti; , Palupi, M.A (2015)
Yemen ethnic are comer ethnic and live in Indonesia around 15th century. Until now, this ethnic are hereditary have a descent and now the populations of Yemenis are very high. Many populations of Yemenis make a spread of Yemen settlement on some city, one of them is in Pasar Kliwon Surakarta. On a cultural issues, Yemenis are very strong to keep their ethnic purity, one of them is prohibit intercultural marriage. Power of this etnic on keep their purity lead to big resistance when intercultural marriage implemented. From the fact about Yemen ethnic researcher set the aim of this research, is how communication pattern on inter-ethnic marriage of Yemen ethnic with descriptive qualitative method and Miles huberman analysis model. Theory that used on this research is cultural conditioning by Deddy Mulyana, ethnicity by Marcus Bank, and Intercultural marriage value by Frame. Result of this research show that resistance still exist on some family, smallest resistance is rejection to communicate and biggest resistance is expulsion from house.